Aplikasi Sirkulasi Kualitatif pada Interior Ciputra World Mall Surabaya - Laurensia Devina Wijaya; Sriti Mayang Sari; Celline Junica Pradjonggo (Intra, 2019)
Ciputra World Mall is one of the high-end malls in Surabaya that has enhanced Surabaya's reputation as the more modern and international class city that has 6 floors, integrated by horizontal & vertical circulation. Circulation is an element that regulates & connects different parts of shopping centers such as anchor stores, secondary anchors, landscaping and other facilities. Organizing circulation according to Peter Coleman was identified as a functional and qualitative circulation requirement. Qualitative circulation requirements are the second recommended planning consideration for mall design details. In general, qualitative circulation requirements gives a character to a place and helps the facilities easier to be remembered. Qualitative requirements is more about the consideration of the mall usage from the visitor's point of view and to make a difference between one mall to another (Coleman, 2006). This research uses a descriptive qualitative research method. This research aims to find out the application of qualitative circulation in the interior of Ciputra World Mall Surabaya. The results obtained from this research shows that "Ciputra World Mall" applies the qualitative circulation requirements according to the parameters.